2015
DOI: 10.1097/md.0000000000001909
|View full text |Cite
|
Sign up to set email alerts
|

DTI Study of Cerebral Normal-Appearing White Matter in Hereditary Neuropathy With Liability to Pressure Palsies (HNPP)

Abstract: The majority of previous studies on hereditary neuropathy with liability to pressure palsies (HNPP) were focused on peripheral nerves, whereas cerebral alterations in HNPP have been less attended to. In this work, Diffusion tensor imaging (DTI) was used to detect the changes in WM, especially in the normal-appearing white matter (NAWM) in HNPP patients for its sensitivity in probing the microstructure of WM, the sensitive metric was searched for probing cerebral alterations and the regional distribution of cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Recent studies suggested the important involvement of the CNS in most patients with PMP22 deletion (18, 19). This is supported by prolonged latencies of visual evoked potentials, neurochemical alterations with decreased N -acetylaspartate (NAA) and creatine (Cre) concentrations, white matter (WM) volume reduction detected by cMRI, cognitive impairment (in 70% of patients), and fractional anisotropy alteration in several WM regions (e.g., in the columns of the fornix) (1820). A large family study described CNS involvement and WM lesions predominantly in the subcortical frontal WM (21).…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies suggested the important involvement of the CNS in most patients with PMP22 deletion (18, 19). This is supported by prolonged latencies of visual evoked potentials, neurochemical alterations with decreased N -acetylaspartate (NAA) and creatine (Cre) concentrations, white matter (WM) volume reduction detected by cMRI, cognitive impairment (in 70% of patients), and fractional anisotropy alteration in several WM regions (e.g., in the columns of the fornix) (1820). A large family study described CNS involvement and WM lesions predominantly in the subcortical frontal WM (21).…”
Section: Discussionmentioning
confidence: 97%
“…With respect to frontal regions, hereditary neuropathy has been associated with white matter disturbances in frontal regions (Wang et al, 2015); both chemotherapy-induced (Boland et al, 2014, Nudelman et al, 2016) and diabetic (Li et al, 2018, Manor et al, 2012) neuropathies show altered frontal activity. Furthermore, frontoparietal regions are relevant to encoding vibrotactile stimuli (Woolgar and Zopf, 2017) (see also, Godde et al, 2010, Wu et al, 2018, Fassihi et al, 2017, Ku et al, 2007, Soros et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a recent report about fractional anisotropy abnormalities in central nervous system white matter detected with diffusion tensor imaging in HNPP patients. [ 41 ] Alternatively, the detected MRS alterations might reflect functional changes resulting from altered nerve conduction in HNPP patients rather than structural changes.…”
Section: Discussionmentioning
confidence: 99%